The effect of fullerenol C60 on skeletal muscle after lower limb ischemia reperfusion injury in streptozotocin-induced diabetic rats - Kartal, Hakan; Küçük, Ayşegül; Kılıçarslan, Aydan; Polat, Yücel; Süngü, Nuran; Kip, Gülay; Arslan, Mustafa (Journal of Surgery and Medicine, 2020)
Aim: Fullerenol, a water-soluble C60-fullerene, has been demonstrated to scavenge free radicals in vitro and in vivo. The aim of the study was to investigate the effects of fullerenol C60 on lower skeletal muscles in a rat model of ischemia/reperfusion (I/R). Methods: After approval of the ethics committee, 30 Wistar Albino rat were divided into 5 groups with six animals per each as follows: Control (C), diabetes (D), diabetes+fullerenol C60 (DF), diabetes+I/R (group DIR) and diabetes I/R+fullerenol C60 (DIR-F) groups. Streptozotocin was administered to the rats to induce diabetes at a dose of 55 mg/kg. Four weeks after the onset of diabetes, rats were subjected to 2 hours of ischemia and 2 hours of reperfusion. At the end of the reperfusion period, skeletal muscle samples were taken from the lower extremity in all groups for histopathological and immunohistopathological examinations. Results: Myositis and endothelial caspase 3 enzyme activities were high in all groups, particularly DIR. Compared to C, DF and DIR-F groups, inflammation and myositis were significantly higher in the DIR group (P=0.001, P=0.006, P=0.001, respectively, and P=0.001, P=0.022, P=0.001, respectively). Vascular dilatation and congestion were significantly more prominent in all groups compared to the control group (P=0.001 for all). Conclusion: Our results confirm that fullerenol C60 has protective effects against skeletal muscle damage resulting from I/R in diabetic rats. Future studies conducted to evaluate these effects may help illuminate the action mechanism of fullerenol C60 and pathophysiology underlying the tissue damage related to I/R injury.